최한기의 기학적 인성교육론 - 이영찬(Lee young chan) (한국학논집, 2017)
인성교육에는 그 사회의 역사․문화적 가치와 시대적 요구가 반영되기 마련이다. 한국사회는 그간 급속한 산업 구조적 변화를 겪어왔고 어느덧 세계화사회와 다문화사회로 깊숙이 진입하고 있다. 세계화와 다문화적 추세는 인성개념에 있어 아노미적 상황을 초래했고 이에 따른 한국적 인성교육에 대한 정체성 확립이 요청되어 왔다. 본고는 최한기(1803-1877)의 기학적 인성교육 사상과 이론을 살펴보고 이것이 현대적 인성덕목과 인성교육에 주는 함의를 밝혀보고자 하였다. 최한기는 기학적 인간관을 통해 인성을 규정하고 이것을 성리학적 성품이라기보다 기품으로 파악하였다. 그는 인성을 대기의 활동운화적 본성이 체화된 신기의 본성으로 보았고 개인의 인성 특성은 타고난 천기(천성), 토질(환경), 부모의 정혈(유전자), 그리고 습염(학습)의 차이에 기인하는 것이라 보았다. 따라서 기학적 인성교육도 도덕적 본성에 따른 심교心敎가 아니라 신기운화에 의거하는 기교氣敎가 되어야 함을 강조하였다. 최한기의 인성교육은 운화와 인도를 통합하는 기화인도교를 목표로 하였다. 운화에 승순하여 인도에 화합하는 것이 덕행이고, 운화를 사용하여 인도를 돕는 것이 재능이다. 그는 이를 위해 기품, 견문, 존양, 삼등운화 등 이른바 사절四節을 교육해야 한다고 보았다. 기학적 인성교육은 사절의 교육내용을 완성할 때 기화와 인도가 통합되는 기화인도교를 성취할 수 있다. 그리고 그는 인성교육 방법으로써 추측의 방법을 제시했다. 추측으로 운화의 이치[추측지리]를 얻고 운화를 승순하는 것으로써 사람을 가르치는 것이 가장 잘 가르치는 방법이기 때문이다. 그는 추[미룸]의 방법으로 박학博學, 심문審問, 성경誠敬, 강습講習 등을 들었고, 측[미룸]의 방법으로 반관反觀, 무아無我, 궁리窮理, 증험證驗, 미발未發 등을 들었다. 그리고 스승으로서도 운화에 승순하는 기사氣師를 으뜸으로 여겼고, 교육도 학생의 기질에 따른 운화교육을 강조했다. 최한기의 인성교육론은 현대 한국인의 전통적 인성 가치와 덕목을 이해하고 한국적 인성교육의 필요성을 인식하는 계기를 제공했다. 특히 그의 기학적 인성교육론은 현대 인성교육에 있어 신기 교육, 전인 교육, 생태 교육, 영성 교육에 대해 시사하는 점이 많았다. Personality education is a reflection of the historical and cultural value and the needs of a society. The Korean society underwent rapid changes in the industrial structure and moved deeply into the global and multicultural society. The global and multicultural trend have led to anomic situation in personality concept and have asked to establish a korean identity for character education. This paper examined Choe han-ki(1803-1877)' personality education ideas and theories and tried to explain the implications of modern personality virtues and personality education. Choe han-ki defined human personalities through kihak' human beings view and understood them with sung poom(性稟) rather than ki poom(氣稟). He attributed human personality to the nature of sin-ki(神氣) that is internalized the Hwal-dong-un-hwa(活動運化) nature of atmosphere ki(大氣), and the personality characteristic of the individual is based on the differences between Heaven ki(天氣), Earth ki(地氣), parents ki(血氣) and learning(習染). Therefore, personality education also emphasized that it should be a kikyo(氣敎) that relies on sinki- unhwa(神氣運化) rather than simkyo(心敎) that depends on moral nature. Choe han ki' personality education aimed at the Kihwa-indo-gyo(氣化人道敎), which integrates unhwa(運化) and human way(人道). It is dukheang(德行) that human law is good for the natural law, and it is jeneng(才能) to practice human law using natural law. He offered Sajeol(四節) like as kipoom(氣稟), keonmoon(見聞), jonyang(存養), Samdeng-unhwa(三等運化) as an educational content. Kihak personality education can be achieved Kihwa-indo-gyo by completing Sajeol. And his personality education method depended on Chu-chek method. It is because teaching is taught well by guessing unhwa(運化) and teaching person by unhwa. He listed bakhak(博學), simmun(審問), sungkyung(誠敬), gangseb(講習) as a method of chu(推), and bankwan(反觀), mua(無我), gungli(窮理), jenghum(證驗), mibal(未發) as a method of chek(測). He regarded kisa(氣師) as a priority teacher, and emphasized that education should be done according to the student’s temperament(氣質). From now on, Choe han-ki's personality education theory provided an occasion to understand the traditional personality values and virtues of modern Koreans and recognize the necessity of Korean character education. In particular, his personality education suggested a lot of emphasis on sinki(神氣) education, ecological education, and spiritual education in modern personality education. KCI Citation Count: 0